The role of remote data capture, wearables, and digital biomarkers in decentralized clinical trials - Chodankar, Deepa; Raval, Tapan K.; Jeyaraj, Jeyaseelan (Perspectives in clinical research, 2024)
Abstract Decentralized clinical trials (DCTs) are gaining momentum in clinical research as these studies can be executed remotely through telemedicine and mobile/local health-care providers. The COVID-19 pandemic has further accelerated advances and adoption in this area. In the past few years, there has been significant development and growth in the use of remote data that are electronically transmitted from a clinical trial (CT) participant, from outside the clinical setting, to a data repository. Such data may include laboratory data, safety data, or outcome measures reported by the participant, the clinician or the observer. Similarly, wearable health monitoring devices are being increasingly used in health-care and CT settings. Digital biomarkers, which can support continuous measurement of physiologic parameters outside the physical confines of the clinical environment, are also creating new and improved opportunities for patient care and biomedical research, enabling remote monitoring and DCTs. There are several benefits to using remote data capture, wearables, and digital biomarkers in clinical health-care research; however, several questions and challenges still need to be addressed. In an effort to understand the adoption of these technologies in DCTs, and the challenges therein, the authors of this workstream conducted an online survey of clinical research stakeholders across India and reviewed 80 responses. The review article summarizes the key findings from this online survey.